Climate variability and its impacts on water resources in the Upper Indus Basin under IPCC climate change scenarios. (2015) - Khan, Firdos; Pilz, Jürgen; Amjad, Muhammad; Wiberg, David A.
The output of a regional climate model (RCM), providing regional climate for impact studies (PRECIS), is used as input data to the hydrological model to produce inflow projections at the Tarbela Reservoir on the Indus River. Maximum temperature, minimum temperature and precipitation are investigated for possible climate change in the region. The hydrological model was calibrated for the 1995-2004 period and validated for the 1990-1994 period with almost 90% efficiencies. The projections of inflow to the Tarbela Reservoir show that there is an overall increase of 59.42% and 34.27% to the Tarbela Reservoir during the period of 2040-2069 under the A2 and the B2 scenarios, respectively. There will be much more water available in the future, with the highest inflow and comparatively more water shortage noted in the 2020s under the A2 scenario. Finally, the impacts of changing climates on the operation of Tarbela Dam are investigated.